Mudflows under changing climate in Zailiysky Alatau, Northern Tien Shan (Journal of Nepal Geological Society, 2006)
The influence of climate change on mudflows is evident on the northern slopes of the Zailiysky Alatau Mountain Range. In this area, most of the mudflows occurred during the Riss- Wurm interglacial period whereas they nearly stopped during the Riss and Wurm Ice Ages. The amount of sediment transported by mudflows to the debris cones located on the foothills increased significantly when the summer air temperature increased by 2-3 °C. Under such conditions, dams are ineffective to control mudflows. Hence, for an effective mudflow control strategy, it is necessary to estimate their frequency and magnitude.